Features of the Neonatal Period in Perinatally HIV-Exposed Children Receiving Combined Сhemoprophylaxis of mother-to-child Transmission of HIV - A. S. Vanyarkina; A. G. Petrova; L. V. Rychkova; E. V. Moskaleva; E. A. Novikova (Acta Biomedica Scientifica)
The aim. To study the features of the course of the neonatal period in children, perinatally exposed to HIV, who receive an enhanced regimen of chemoprophylaxis of HIV mother-to-child transmission.Patients and methods. A retrospective longitudinal cohort study of mother – child pairs for the period from 2017 to 2019 was carried out. The clinical observation group included HIV-positive women with a high risk of vertical transmission of the immunodeficiency virus (n = 213) and their newborn children (n = 214), who were prescribed an enhanced chemoprophylaxis regimen of HIV transmission from mother to child. Results. According to the results of the study of HIV-positive mothers we revealed a high prevalence of secondary diseases and a high per partum viremia – 1700 (222–18342) copies/ml. 35.9 % of children were born prematurely, 27.5 % – had low birth weight by gestational age. In newborns, diseases of the respiratory (24.3 %) and nervous (17.2 %) systems prevailed. 17.2 % of children developed intrauterine infection; HIV RNA was detected in 3.7 %. Congenital malformations were observed in 7.4 % of children. Symptoms of enteropathy were noted in 24.7 % of newborns. A decrease in red blood counts was found in all children by the 28th day of life (pw < 0.001).Conclusion. The study confirms the need for increased attention and improvement of approaches to medical support of children who were perinatally exposed to high risk of vertical HIV infection.